Going to Mars : the Nikki Giovanni project [videorecording (DVD)] - Giovanni, Nikki; Henson, Taraji P. (Kino Lorber, 2024)
Shortlisted for an Academy Awardʼ for Best Documentary Feature and winner of the Sundance Grand Jury Prize, Going to Mars: The Nikki Giovanni Project is a beguiling documentary portrait that follows poet and activist Nikki Giovanni as she approaches 80. The film explores Giovanni's Afrofuturist-feminist philosophical outlook as well as her poignant relationship with her family, her political audacity, and her poetic eloquence, all knit together with a constant eye and ear for its subject's own aesthetic verve. Looking back at a personal life and history cast in the long shadow of American racism, and forward to hopeful, possible futures, Giovanni acts as our guide and narrator, with refreshingly unorthodox filmmakers Joe Brewster and Michl̈e Stephenson refraining from traditional chronologies or talking-head conventions. Going to Mars is fueled by constant intellectual engagement and radical imagination in the search for emotional and political fulfillment in a world of disenfranchisement.